Study of Repeat Breeder of Dairy Cows in Farmer Level - Surya Agus Prihatno; Asmarani Kusumawati; Ni Wayan Kurniani Karja; Bambang Sumiarto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
One of the important reproductive disorders in dairy cows was repeat breeding. Economic losses was quite high, due to the low reproductive efficiency and productivity. Breeder is one of the risk faktors on the incidence of repeat breeding. The aims of this research were to determine the incidence of repeat breeding cases in dairy cattle at Special Regency of Yogyakarta (DIY) and many factors from the farmers and dairy cattle aspects that caused the cases. In this study, 401 traditional farmers at DIY were used. The method of data collection was done by interviewing the farmers and direct observation to the dairy cattle. The data consist of farmer education level, length period of farming experience, stall condition, length distance from inseminator, estrous detection ability,knowledge of estrous, estrous observation by farmer, stall cleanliness, cattle cleanlines, and squeezing time.Data were collected on a descriptive analysis of each variable studied. Analysis used logistic regression models to analyze the faktors that influence the incidence of repeat breeding. The sensitivity and specificity of the models were analyzed by Lemeshow goodness of fit test.The result of this study showed that the prevalence of repeat breeding in dairy cattle from farmer aspect was 29.4%. The factor from farmer aspect which affected repeat breeding cases was estrus detection once per day(coefficient regression 4.09563, OR=60,1), detection of estrus twice daily (+ 2.92553, OR=18.6) , disordersof pregnancy (+2.22630, OR= 9.3), dirty environment (+0.91889, OR=2,5), worst drainage (+2.58072, OR=13,2), and education (+1.31295, OR=3,7). It was concluded that the prevalence of repeat breeding at DIY as big as 29.4%. Risk factors affecting the repeat breeding were estrus detection once per day, detection of estrus twice a day, dirty environment, worst drainage, and education. Keywords : prevalency, repeat breeding, dairy cattle, logistic regression, odds ratio